2007
DOI: 10.4161/cc.6.16.4564
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Influenza A Virus Matrix Protein 2 for Mammalian Cells is Associated with its Intrinsic Proton-Channeling Activity

Abstract: Key wORdSinfluenza virus, matrix protein 2, proton channel, cytotoxicity AcKnOwLedGeMenTSWe thank Michael Sherman (Boston University) for helpful comments and discussion and Ivan Adzhubei (Harvard Medical School) for the help with M2 three-dimensional structure modeling. This work was funded in part by NIH grant 5R43AI063634-02 to P.I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…This may explain the unique M1 mRNA splicing kinetics in which M1 production predominates early in infection when NS1 synthesis is low, and then M1 to M2 mRNA splicing is likely enhanced by the high levels of NS1 at late stages of infection 37 . M2 protein has been shown to be cytotoxic to cells when expressed alone 38 , which suggests that M2 levels need to be tightly regulated during infection. Furthermore, M2 is critical for viral budding 39 , indicating that timing of expression is likely important for production of infectious viral particles, as premature synthesis could lead to defective particles.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the unique M1 mRNA splicing kinetics in which M1 production predominates early in infection when NS1 synthesis is low, and then M1 to M2 mRNA splicing is likely enhanced by the high levels of NS1 at late stages of infection 37 . M2 protein has been shown to be cytotoxic to cells when expressed alone 38 , which suggests that M2 levels need to be tightly regulated during infection. Furthermore, M2 is critical for viral budding 39 , indicating that timing of expression is likely important for production of infectious viral particles, as premature synthesis could lead to defective particles.…”
Section: Discussionmentioning
confidence: 99%
“…The AIV M2 protein was found to be weakly immunogenic and did not induce neutralizing antibodies but reduced virus replication in mice, a nonnatural host (18). Various vaccine approaches have been evaluated for development of an M2 universal vaccine, including passive transfer of M2-specific antibodies (23,41) or immunization with conjugated M2 peptide antigens (7,26), complete M2 protein (16), or the external domain of M2 (5,10,16). Although these studies demonstrated protection against influenza virus challenge in the nonnatural mouse host, the role of M2 protein in immunogenicity and protection in a natural host had not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emergence of widespread highly virulent adamantane-resistant strains such as avian and swine influenza virus strains (9,10) has prompted the need for newer antivirals. Drug discovery efforts targeting M2 have been difficult due to the toxicity of M2 in cells (11), the difficulty of reconstituting M2 in liposomes for largescale application (12,13), and the labor-intensive, low-throughput electrophysiological approaches typically used to study ion channels.…”
mentioning
confidence: 99%